GENETIC DIVERSITY STUDIES FOR ECONOMICALLY IMPORTANT TRAITS IN RICE USING PRINCIPAL COMPONENT ANALYSIS - C. KIRAN KUMAR REDDY*and A. PRATAP KUMAR REDDY, (The Journal of Research ANGRAU, 2019)
Genetic diversity in rice using principal component analysis in 86 advanced breeding lines developed atAgricultural Research Station, Utukur and 7 popularly grown varieties was studied. The analysis of variance revealedsignificant differences for all the nine economically important yield traits measured. Use of principal componentanalysis revealed nine components, out of which three components with eigen values greater than one (1) couldexplain 57% of the variability.Based on the loading scores, characters viz., panicle weight, panicle length, number offilled grains per panicle were found to be most contributing towards the construction of the first principal component.Also, different entries viz., UTR 83-1, UTR 256 (high yield), UTR 258, UTR 209, UTR 202 (higher tiller number), UTR224, UTR 253, UTR 257 (higher panicle weight), UTR 224, UTR 253, UTR 257 (higher panicle length), UTR 253, UTR218, UTR 222 (lower test weight indicating fine grain nature) and UTR 224, UTR 253 and UTR 217 (higher filledgrains panicle-1) were identified.